Pelatihan Desain Konten Pembelajaran yang Kreatif dan Inovatif berbasis Aplikasi Moodle - Estika Satriani; Sri Wahyuni; Muklis Muklis (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
The purpose of this community service is to increase teachers' understanding and skills in designing creative and innovative learning content using the Moodle application. The method used in this service is training with a classical and individual approach. The service partners are 15 (fifteen) teachers ofÂ Budhi Darma Dumai SMKS. The instrument for evaluating this activity uses a questionnaire and is analyzed with an interval assessment. The results of this service show that 85% of teachers are able to design learning with creative and innovative content. Training on designing creative and innovative learning content through the Moodle application is proven to have increased teacher knowledge and skill development in utilizing technology in learning.